The report of the London Committee appointed to investigate the late charges made against the Norwich Union Fire and Life Office . presented to a meeting of insurers, held at the City of London [...], on [...] the 25th of September, 1919: together with the resolutions of the meeting adopted thereon. And an appendix of documents, &c.; (Bensley, 1818)
Norwich Union Fire and Life Insurance.